Effects of scrap rubber waste on the mechanical performance of mortar made of crushed sand and sediment - Hadj Mostefa, Adda; Balegh, Benamar; Sellaf, Hamid; Dahamni, Mohamed Elamine (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The consumption of natural sand in Algeria is high due to its extensive use in mortar, while sediments and rubber waste pose significant environmental and societal challenges. This study investigates the effects of incorporating rubber waste content in mortars mixed with crushed sand and sediment. The primary goal is to valorize crushed sand particles through physical and mechanical tests, evaluating their potential as an alternative to natural sand in mortar mixtures.Methods: Experimental work was carried out to study the impact of partially and fully replacing sediments with crushed sand particles in mortar mixes. Mortar mixtures were prepared using different sediment-to-crushed sand ratios (10%, 25%, 35%, 50%, and 100%) to observe their influence on physical and mechanical properties. Additionally, the effects of adding 2%, 4%, and 6% granulated rubber to the optimal mortar were analyzed. Various tests, including those tsting compressive strength, flexural strength, and ultrasonic pulse velocity, were performed to evaluate the performance of the mixtures.Results: The results indicated that replacing sediment with crushed sand improved the strength properties of mortar, particularly due to better particle packing. The mortar containing 65 wt% sediments and 35 wt% crushed sand showed properties similar to the reference mortar. The addition of rubber waste increased compressibility but enhanced mechanical properties when used in moderation. Ultrasonic pulse velocity decreased with higher crushed sand content, and the porosity of the mixtures was reduced.Conclusions: Crushed sand and sediment particles are effective fillers for mortar, ensuring good performance and improved strength. The efficiency of these materials depends on their morphology and genesis. The study demonstrates that crushed sand can be a viable alternative to natural sand, and rubber waste can be used as a reinforcing material in mortar, though its proportions should be carefully controlled to avoid negative effects on mechanical properties.
Keywords: mortar; sediment; crushed sand; scrap rubber waste; compressive strength; tensile strength